Hebrew infusion : language and community at American Jewish summer camps - Benor, Sarah, 1975-; Krasner, Jonathan B.; Avni, Sharon, 1970- (Rutgers University Press, 2020)
"Each summer, tens of thousands of American Jews attend residential camps, where they may see Hebrew signs, sing and dance to Hebrew songs, and hear a camp-specific hybrid language register called Camp Hebraized English, as in: "Let's hear some ruach (spirit) in this chadar ochel (dining hall)!" Using historical and sociolinguistic methods, this book explains how camp directors and staff came to infuse Hebrew in creative ways and how their rationales and practices have evolved from the early 20th century to today. Some Jewish leaders worry that Camp Hebraized English impedes Hebrew acquisition, while others recognize its power to strengthen campers' bonds with Israel, Judaism, and the Jewish people. Hebrew Infusion explores these conflicting ideologies, showing how hybrid language can serve a formative role in fostering religious, diasporic communities. The insightful analysis and engaging descriptions of camp life will appeal to anyone interested in language, education, or American Jewish culture"--Provided by publisher